How To Raise Successful People - Wojcicki, Esther (New York HarperCollins, 2019)
The Godmother of Silicon Valley, legendary teacher, and mother of a Super Family shares her tried-and-tested methods for raising happy, healthy, successful children using Trust, Respect, Independence, Collaboration, and Kindness: TRICK.Esther Wojcicki$1 (3z(BWoj(3y (Bto her many friends and admirers$1 (Bis famous for three things: teaching a high school class that has changed the lives of thousands of kids, inspiring Silicon Valley legends like Steve Jobs, and raising three daughters who have each become famously successful. What do these three accomplishments have in common? They$1 (Bre the result of TRICK, Woj$1 (Bs secret to raising successful people: Trust, Respect, Independence, Collaboration, and Kindness. Simple lessons, but the results are radical. Wojcicki$1 (Bs methods are the opposite of helicopter parenting. As we face an epidemic of parental anxiety, Woj is here to say: relax. Talk to infants as if they are adults. Allow teenagers to pick projects that relate to the real world and their own passions, and let them figure out how to complete them. Above all, let your child lead. How to Raise Successful People offers essential lessons for raising, educating, and managing people to their highest potential. Change your parenting, change the world.s
Keywords: Psychology; Psychology-Conscious & The Self; Motivation